Thermodynamic resource theories, non-commutativity and maximum entropy principles. (6th April 2017) - Lostaglio, Matteo; Jennings, David; Rudolph, Terry
Abstract: We discuss some features of thermodynamics in the presence of multiple conserved quantities. We prove a generalisation of Landauer principle illustrating tradeoffs between the erasure costs paid in different 'currencies'. We then show how the maximum entropy and complete passivity approaches give different answers in the presence of multiple observables. We discuss how this seems to prevent current resource theories from fully capturing thermodynamic aspects of non-commutativity.